A teaching program based on experiential learning and its effectiveness in developing strategic competence and productive thinking in the mathematics curriculum among sixth-grade students in Hail - Alhowishel, Howishel Saud (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to develop an instructional program based on experiential learning and to examine its effectiveness in enhancing strategic competence and productive thinking in the mathematics curriculum among sixth-grade students in the city of Hail. To achieve this goal, the study adopted a quasi-experimental design. The research instruments included a test for strategic competence and a test for productive thinking skills. The study was conducted on a sample of (79) sixth-grade students. The findings reveal the following:-There was a statistically significant difference at the level (α ≤ 0.05) between the mean scores of the experimental and control groups in the post-test of strategic competence in favor of the experimental group.-There was a statistically significant difference at the level (α ≤ 0.05) between the mean scores of the experimental and control groups in the post-test of productive thinking skills in favor of the experimental group.Based on these results, the study recommended several actions, most notably: utilizing the instructional program based on experiential learning to enhance strategic competence and productive thinking skills, given its engaging and stimulating nature in the educational process, which boosts students' motivation to learn. The study also recommended enriching the mathematics curriculum with content aligned with experiential learning and making use of the prepared program guide in organizing training workshops to improve mathematics education.
Keywords: Experiential Learning; Strategic Competence; Productive Thinking Skills